Assistance in the Development of Deep Learning–Based Instructional Tools for Junior High School Science Teachers in Pacitan Regency - Sarwanto Sarwanto; Widha Sunarno; Sukarmin Sukarmin; Pujayanto Pujayanto; Elvin Yusliana Ekawati; Daru Wahyuningsih; Indhah Permatasari; Linda Dwi Astuti (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2026)
This community service program aims to support junior high school science teachers across Pacitan Regency in developing instructional tools grounded in deep learning principles. The program adopted a Participatory Action Research (PAR) approach implemented through systematic training and mentoring activities involving 74 science teachers. The activities were organized into two main sessions. The first session focused on enhancing teachers’ conceptual understanding and providing practical guidance in designing deep learning–oriented instructional tools. During this stage, participants developed initial drafts that emphasized higher-order thinking skills, inquiry-based learning strategies, and the integration of digital media. The second session consisted of collaborative evaluation and refinement of the drafts through feedback from facilitators and fellow participants. The evaluation process employed facilitator assessment instruments to examine the alignment of the instructional tools with deep learning principles, along with participant questionnaires to document teachers’ perceptions and learning experiences. Quantitative data obtained from the questionnaires were analyzed using descriptive statistics, while qualitative feedback from facilitators and participants was examined to support the interpretation of the findings. As a result, each participant produced a finalized deep learning–based instructional tool tailored to the specific needs of their classroom context. The findings indicate that 95.67% of participants rated the program as very good, and 93.4% reported an increased understanding of deep learning concepts. To ensure the sustainability of the program outcomes, all finalized instructional tools will be compiled into a single volume and submitted for ISBN registration. Overall, this initiative enhanced teachers’ pedagogical and technological competencies and provides a replicable model of professional development for other science education contexts.